Progresinio gyventojų pajamų mokesčio įtakos Lietuvos nacionalinio biudžeto pajamoms tyrimas - Povilaikaitė, Agnė (Institutional Repository of Kaunas University of Technology, 2015)
The Republic of Lithuania Law on Income of Individuals was accepted in 2003 and since then has been adjusted 63 times. Frequent changes of the income tax treatment cause difficulties for both taxpayers and tax administrators. Moreover the changes affect Lithuanian national revenue collection. In order to improve collection of tax revenues, it is essential to implement the reform of the tax system. During pre-election period, most of political parties in their election campaign emphasize the necessity and benefits of progressive personal income tax rate. This issue has repeatedly been raised at meetings of the Seimas where politicians suggest the personal income tax conversion projects. On the other hand, in estimation of several financial analysts and economists implementation of progressive income tax raise doubts about the benefit of progressive personal income tax rates in Lithuania. Different opinions raise the debate and require researches which estimate the effect of the progressive personal income tax rates on public finances. Research object – the impact of progressive personal income tax on Lithuanian national budget revenue. Research aim – to evaluate the impact of implementation of progressive personal income tax rates on Lithuanian national budget revenue. Research results: 1. The analysis of the national implementation of personal income tax peculiarities shows that the progressive personal income tax rates apply to twenty-four countries, whereas the proportional personal income tax rate to seven countries. Northern countries apply a dual income tax system, under which wages subject to progressive, while income from capital - proportional personal income tax rate. In order to assess the tax impact of the budget income, calculated two relative ratios: PIT tax revenue to GDP ratio and PIT tax revenue ratio of all tax revenues. The first value of relative indicator was highest in Scandinavian countries, Belgium, Italy and Iceland, and the second – in Denmark, Iceland, Ireland and Switzerland. The ...